2022
DOI: 10.1111/padm.12889
|View full text |Cite
|
Sign up to set email alerts
|

Administrative characteristics and timing of governments' crisis responses: A global study of early reactions to COVID‐19

Abstract: In a crisis, fast reaction is key. But what can public administration tell us about this? This study develops a theoretical framework explaining how administrative characteristics, including fragmentation, capacities, legacies and learning, affect governments' response timing. The COVID‐19 pandemic is exploited as a unique empirical setting to test this framework and its scope conditions. Region fixed‐effects models and survival analysis of partly hand collected data for more than 150 national governments conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In addition, there was adequate financial support, including subsidies for participating personnel, food and beverage expenses for all students during the closure period, expenses for daily necessities and financial subsidies for students from low‐income families. Similar to France and Germany, China responded more quickly to the COVID‐19 crisis than other more decentralised countries (Jugl, 2022). Furthermore, the intervention involved cooperation between multidisciplinary experts, similar to the model proposed for urgent psychological support during the COVID‐19 pandemic in Tunisia (Zgueb et al, 2020).…”
Section: Intervention Programme and Discussionmentioning
confidence: 99%
“…In addition, there was adequate financial support, including subsidies for participating personnel, food and beverage expenses for all students during the closure period, expenses for daily necessities and financial subsidies for students from low‐income families. Similar to France and Germany, China responded more quickly to the COVID‐19 crisis than other more decentralised countries (Jugl, 2022). Furthermore, the intervention involved cooperation between multidisciplinary experts, similar to the model proposed for urgent psychological support during the COVID‐19 pandemic in Tunisia (Zgueb et al, 2020).…”
Section: Intervention Programme and Discussionmentioning
confidence: 99%
“…Compared to reductions in force, wage cuts can be implemented with relative ease and are less likely to elicit political opposition from employees and unions (IMF, 2022). The findings suggest, however, such cuts would be unwise when it comes to delivering labor‐intensive public services (see also Jugl, Forthcoming). If borrowing or other measures are not sufficient and a reduction in wages becomes necessary, the World Bank (2020) recommends delaying cuts until a country enters a recovery and avoiding across the board cuts to protect the wages of employees providing essential services.…”
Section: Discussionmentioning
confidence: 99%
“…A study of COVID-19 responses of 150 national governments revealed that awareness of the crisis, appraisal of potential responses and easy mechanisms for collective decision-making reduced the decision time by governments. Countries that had an opportunity to learn from the experiences of others were also found to be better placed in their crisis response to the pandemic (Jugl, 2022). Prior exposure to the same or similar crisis can help by highlighting systemic gaps including capacity constraints in current institutional systems and enhance risk awareness -all contributing to improved crisis preparedness (Zhang et al, 2018;Capano et al, 2020).…”
Section: Policy Learning Under Crisismentioning
confidence: 99%